A framework to retain the knowledge of departing knowledge workers in the manufacturing industry. Issue 4 (10th January 2020) - Sumbal, Muhammad Saleem; Tsui, Eric; Durst, Susanne; Shujahat, Muhammad; Irfan, Irfan; Ali, Syed Muhammad
Abstract : Purpose: The purpose of this study is to develop a conceptual framework on knowledge loss in a manufacturing sector based on three aspects: likelihood of knowledge loss, critical areas of knowledge loss and relevance of each of these knowledge areas in terms of utilization and alignment with organizational goals and strategy. Such a conceptual framework can be helpful to the practicing managers in understanding the types of knowledge that is lost of a given departing employee and thus deciding on a measure to retain the critical employees or capture their knowledge before they leave. Design/methodology/approach: Using a case study approach, data has been collected from a multinational battery manufacturing company based in Hong Kong. Semi-structured interviews have been conducted and analyzed through CAQDAS ATLAS.ti to generate the themes which were then used to develop the conceptual framework. Findings: The findings revealed that the likelihood factors of knowledge loss in the manufacturing sector include layoffs, retirement, immigration and job change. The critical areas of knowledge loss comprise the knowledge of relationships and networks, especially with the customers and suppliers, the technical knowledge (battery and process technology) and knowledge of management, among others. The relevance of each of these knowledge areas needs to be determined through proper analysis whether these knowledge areas are needed in future projects, up to date and aligned with organizational goals and strategy along with other factors. Research limitations/implications: Using the developed conceptual framework, managers and executives can identify critical employees in the manufacturing sector and accordingly take some appropriate measures to retain their knowledge. Caution should be taken while applying the findings of this study in other industries and context. Originality/value: This paper is an attempt to reduce the dearth of empirical studies by exploring knowledge retention in the manufacturing sector, especially in the development of proper conceptual frameworks to assess the potential knowledge loss of employees.